Proceedings of the 12th International Conference on the Evolution of Language (Evolang12) 2018
DOI: 10.12775/3991-1.037
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection in the modern english lexicon

Abstract: This study tests the degree to which the form and function of 54 newly emerging words predicts their success over time in a multi-billion word corpus of American Twitter collected between 2013 and 2016. A linear model of the change in the relative frequency of each word is computed as a function of word length, part-of-speech, word formation process, and meaning. The analysis finds that the most important predictor of the success of these words is marking a new meaning. Shorter words and words created through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Future work should also investigate more semantically-aware definitions of linguistic dissemination. The existence of semantic "neighbors" occurring in similar contexts (e.g., the influence of standard intensifier very on nonstandard intensifier af ) may prevent a new word from reaching widespread popularity (Grieve, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should also investigate more semantically-aware definitions of linguistic dissemination. The existence of semantic "neighbors" occurring in similar contexts (e.g., the influence of standard intensifier very on nonstandard intensifier af ) may prevent a new word from reaching widespread popularity (Grieve, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, they make the case for using largescale web-based corpora for the analysis of lexical change, which the study at hand complies with. Grieve [2018] further analyses the "survival chances" of the lexemes identified by Grieve et al [2017] over a longer time period and investigates which characteristics might contribute to their firm establishment. A similar attempt is made by Stewart & Eisenstein [2018], who try to predict word adoption on Reddit by early dissemination, and by Cole et al [2017], who relate word adaptation to community size on Reddit.…”
Section: Lexical Change In the Online Environmentmentioning
confidence: 99%
“… Grieve et al (2017) develop a procedure to identify emerging words in a corpus of 8.9 billion Twitter messages, based on initially low frequency and a high increase in frequency over a given time period. In a follow-up study, Grieve (2018) predicts the further success of 54 emerging words identified in Grieve et al (2017) as a function of word length, part-of-speech, underlying word-formation process, and novelty of the word’s referent. The latter predictor is shown to be particularly relevant in determining the frequency development of innovative words, whereas part-of-speech does not appear to play a significant role.…”
Section: Introductionmentioning
confidence: 98%